Nivel de Motivación de Logro, Afiliación, Poder y Reconocimiento en Adolescentes entre los 12 Y 17 Años, de la Institución Educativa de la Vereda Sausagua del Municipio de Quinchía, Risaralda. (2023)
Starting at the importance of motivation in students' academic performance, a study takes place with the objective of describing the achievement motivation, affiliation, power and acknowledgment in function of the sociodemographic characteristics of adolescents within 12 and 17 years old from Sausagua's educational institution from Quinchía, Risaralda's municipality. To do that, a quantitative methodology was adopted, with a descriptive method and a group of 50 students chosen through a convenience technique to whom a EM1 motivation scale was applied, based in the McClelland model (1985).